Psychological Impact and Mental Health ‎Status during the COVID-19 Pandemic among ‎Jordanian University Students - Alaedein ‎, Jehad; Al Shraifin‎, Ahmad; Alsheikh Ali‎, Ahmad; Abood, Mohammad; Al-Shobaki, Nayfeh (Jordan Journal of Educational Sciences, 2021)
The current study was conducted to evaluate the psychological impact and the status of mental health during the COVID-19 virus pandemic among a convenience sample of university students in Jordan. The study sample consisted of (625) university students. We used the Arabic version of the Impact of Event Scale-Revised (IES-R) and (DASS-21), respectively. The results showed that there were no statistically significant differences between the means of the impact of the event (IES-R) due to the study variables. Also, statistically significant differences were found between the means of the state of mental health (DASS-21), due to the variable of age in favor of those aged 18-23 years in comparison with those aged 24 years and above; also, there were differences attributed to the working condition in favor of those who do not work. The results did not reveal significant differences due to either sex or marital status variables. Additionally, the results showed that intrusive thoughts, arousal and mental illness explained (49.2%) of the variance in the state of mental health (DASS-21). Specifically, intrusive thoughts contributed to the interpretation of (42.1%), the arousal variable contributed to the explanation of (4.9%) and the mental illness variable explained (2.2%) of the total variance of the predictive model